Effects of the Methylammonium Ion Substitution by 5-Ammoniumvaleric Acid in Lead Trihalide Perovskite Solar Cells: A Combined Experimental and Theoretical Investigation - Cardenas-Jiron, G; Urzua-Leiva, R (Royal Society of Chemistry, 2020)
In the last decade, lead triiodide perovskite (APbI3) (A: organic cation) solar cells (PSCs) have been broadly studied due to their promising features related to the low cost, easy manufacturing process, and stability. Strategies to improve the device stability include the application of techniques such as compositional engineering of the cation of these halide perovskites, but it is still a complex task to find the right balance between the stability and power conversion efficiency of materials and complete devices. In this work, we performed a combined study of five samples of [5-AVA(1−x)MAx]PbI3(5-AVA: ammonium valeric acid and MA: methylammonium) withx= 1.0, 0.75, 0.5, 0.25 and 0.0, using X-ray diffraction (XRD) and UV-VIS spectroscopy measurements in combination with periodic density functional theory (DFT) based calculations. Our samples showed an optical bandgap of 1.58 eV and the coexistence of the two phases as observed by XRD analyses. The theoretical results of the bandgaps for the no mixed phases (x= 1.0 andx= 0.0) show good agreement with the experiment, obtaining bandgap values overestimated by 0.18 eV and 0.33 eV, respectively. A direct relation between the number of 5-AVA ions in the samples and the stability of the phases was theoretically found and proved through the increment observed in the bandgap and the cohesive energy. We proposed a compositional strategy for perovskites [5-AVA(1−x)MAx]PbI3withxvalues of at most 0.5, based on the small blue-shift and the low absorbance reduction of the spectrum curve, added to the small phase stabilization found. © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique 2020.